The impact of Mycobacterium tuberculosis on the macrophage cholesterol metabolism pathway - Chen, Zhanpeng; Kong, Xingxing; Ma, Quan; Chen, Jinyun; Zeng, Yuqin; Liu, Huazhen; Wang, Xiaomin; Lu, Shuihua (Frontiers in Immunology, 2024)
Mycobacterium tuberculosis (Mtb) is an intracellular pathogen capable of adapting and surviving within macrophages, utilizing host nutrients for its growth and replication. Cholesterol is the main carbon source during the infection process of Mtb. Cholesterol metabolism in macrophages is tightly associated with cell functions such as phagocytosis of pathogens, antigen presentation, inflammatory responses, and tissue repair. Research has shown that Mtb infection increases the uptake of low-density lipoprotein (LDL) and cholesterol by macrophages, and enhances de novo cholesterol synthesis in macrophages. Excessive cholesterol is converted into cholesterol esters, while the degradation of cholesterol esters in macrophages is inhibited by Mtb. Furthermore, Mtb infection suppresses the expression of ATP-binding cassette (ABC) transporters in macrophages, impeding cholesterol efflux. These alterations result in the massive accumulation of cholesterol in macrophages, promoting the formation of lipid droplets and foam cells, which ultimately facilitates the persistent survival of Mtb and the progression of tuberculosis (TB), including granuloma formation, tissue cavitation, and systemic dissemination. Mtb infection may also promote the conversion of cholesterol into oxidized cholesterol within macrophages, with the oxidized cholesterol exhibiting anti-Mtb activity. Recent drug development has discovered that reducing cholesterol levels in macrophages can inhibit the invasion of Mtb into macrophages and increase the permeability of anti-tuberculosis drugs. The development of drugs targeting cholesterol metabolic pathways in macrophages, such as those targeting ABC transporters and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), as well as the modification of existing drugs, holds promise for the development of more efficient anti-tuberculosis medications.